Process Evaluation for The CGIAR Climate Resilience Initiative Activities in Kenya - Juma, Ogada Maurice (2024)
In response to the threats of climate change, Alliance of Bioversity International and CIAT and its partners launched the CGIAR Research Initiative on Climate Resilience (ClimBeR) in 2022 in Nairobi, Kenya, covering 6 countries (Guatemala, Kenya, Morocco, the Philippines, Senegal, and Zambia). The aim of ClimBeR is to simultaneously transform food, land, and water systems in a climate crisis so as to enhance the resilience of the smallholder production systems. In 2023, ClimBeR initiative commissioned this process evaluation exercise with two main objectives: (1) To assess the adherence to implementation plan, noting any deviations & corrective measures, and (2) To demonstrate how ClimBeR impacts are emerging, highlighting the drivers of and barriers to uptake. The process evaluation used a blend of qualitative and quantitative approaches. The qualitative module involved Key Informant Interviews (KII) with ClimBeR staff and country-level implementing partners and focus group discussions (FGDs) with implementing farming communities. Quantitative module involved household interviews in the communities where the Risk-Contingent Credit (RCC) innovation is being implemented.